Pengembangan Model Kanvas Bisnis pada Komoditi Jambu Kristal di Kebun Paluna Desa Jayi Kecamatan Sukahaji - Rusyanti, Rusyanti; Setiawan, Iwan (Universitas Galuh, 2024)
Paluna orchard is the largest crystal guava garden in Majalengka. The high consumer demand for crystal guava is one of the goals of Paluna orchard to continue to develop is business. In fact, in 2016 the Paluna orchard was able to generate income of 1,3 billion. The problem faced by the Paluna orchard is that income continues to decline every year. Paluna orchard itself still uses a conventional business model, which in its development is not adaptive to market dynamics, so it requires a new business model in developing its business. The objectives of this research are 1) to find out the potential and opportunities for implementing the Business Model Canvas in Paluna orchard. 2) Want to know the development pattern of the Paluna orchard using the Business Model Canvas. The method used in this research is qualitative, while the research technique is a case study. The techniques and data analysis used were participant observation, in-depth interviews, and documentation studies. The results of this research show that the business model canvas is very suitable to be applied in Paluna Orchard. After conducting an analysis using SWOT analysis, consumer feedback, and industry strength, a business model canvas was developed that makes it easier for Paluna Orchard to create new innovations and overcome the problems they face.